I am trying to find the Fourier series for $\sin^a(x)$ where $a$ is an arbitrary integer $\ge1$. Here is what I have done so far:

$$\sin^a(x)= \left(\frac{e^{ix}-e^{-ix}}{2i}\right)^a=(2i)^{-a}(e^{ix}-e^{-ix})^a$$

Fourier series: $\frac{1}{2\pi} \sum_{-\infty}^{\infty} c_n e^{inx}$

\begin{align} c_n & =\frac{1}{2\pi} \int_{-\pi}^{\pi} f(x) e^{-inx} \, dx \\[10pt] & =\frac{1}{2\pi} \int_{-\pi}^{\pi} (2i)^{-a}(e^{ix}-e^{-ix})^a e^{-inx} \, dx \\[10pt] & =\frac{1}{2\pi} (2i)^{-a} \int_{-\pi}^{\pi} e^{-inx} \sum_{k=0}^a \binom{a}{k} e^{(a-k)ix} e^{-kix} (-1)^k \, dx \\[10pt] & =\frac{1}{2\pi} (2i)^{-a} \left[ \sum_{k=0}^a \binom{a}{k} (-1)^k \frac{1}{(a-2k-n)i} e^{(a-2k-n)ix} \right]_{-\pi}^\pi \\[10pt] & =\frac{1}{2\pi} (2i)^{-a} \sum_{k=0}^{a} \binom{a}{k} (-1)^k \frac{1}{(a-2k-n)i} (e^{(a-2k-n)i\pi} - e^{-(a-2k-n)i\pi}) \\[10pt] & =\frac{1}{2\pi} (2i)^{-a} \sum_{k=0}^{a} \binom{a}{k} (-1)^k \frac{1}{(a-2k-n)i} ((-1)^{(a-2k-n)} - (-1)^{-(a-2k-n)}) \\[10pt] & =0 \end{align}

At this point I strongly feel that I have done something wrong. The only idea I have is that $e^{(a-2k-n)ix})=1$ for $(a-2k-n)=0$. Which makes me evaluate the integral incorrectly, since there should be an $x$ term before plugging in $\pi$ and $-\pi$. I do feel like I am missing something, and would be grateful for any advice.


You have $$ \sum_{k=0}^a \binom a k (-1)^k \int_{-\pi}^\pi e^{ix(a-n-2k)} \, dx. $$ And then $$ \int_{-\pi}^\pi e^{ix(a-n-2k)} \, dx = \begin{cases} 0 & \text{if } a-n-2k \ne 0, \\ 2\pi & \text{if } a-n-2k=0. \end{cases} $$ In the sum $\displaystyle \sum_{k=0}^a,$ for which values of $k$ in the range $0,1,2,\ldots,a$ is $a-n-2k$ equal to $0\text{?}$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.